Akumulasi Logam Cu, Cd dan Pb Pada Meiofauna Intertitial Dan Epifit Di Ekosistem Lamun Monotipic (Enhalus Acoroides) - Efendi, Eko (AQUASAINS, 2015)
Enhalus acoroides is water plant intertidal that might be interaction between ecosystem eachother so it have ability to adsorb heavy metal that came from sea water and sediment that can accumulated in roots, leaf and bar ponder. Variation methods used to know distribution of meiofauna as intertitial fauna or epiphytic fauna on seagrass. The concentration of heavy metal of water, sediment and meiofana will be analyzed. The purpose of this research to determined correlation between concentration in seagrass, sediment, water and organism which associated whitin. The result of this research shown that Â concentration of heavy metal Cu, Cd and Pb have a significant correlation between water, sediment, part of seagrass and meiofauna. The value of R2 shown that correlation between water and sediment have bigest value, otherwise theÂ  R2 value of heavy metal shown that Pb is the biggest than Cd and Cu. Concentration heavy metal in seagrass shown that Cu>Cd>Pb and the same condition is also due in meiofauna. Its mean that the heavy metal is bioavailble for accumulation by meiofauna. Meifauna and segrass can be a good bioindicator for environmenta change especially heavy metal.